Initiation Undertaken For the Upliftment of Resettled Tribes in Mysore District (International Journal of Food and Nutritional Sciences, 2023)
The Paper tries to analyse and measure the undertaken for the Upliftment of Resettled tribes In Mysore District. The tribes of Hunsur and Heggadadevana Kote taluk were Resettled with Beneficiary Oriented Tribal Development schemes have been supporting the resettled tribes. Several enduring schemes have been unleashed to ensure all round development of tribal people. But, the tribal people’s complaints about delay and hindrances in getting rehabilitation benefits are growing. The complaint that government has failed to provide them with benefits as promised. The challenge of brining greater socio economic benefits to all tribes of needs furthering strengthening of the government schemes and collaborative support from NGOs will assist to alleviate the socio economic conditions of the tribals. The Government needs to address these challenges on priority.